Gait characteristics and effects of early treadmill intervention in infants and toddlers with down syndrome: a systematic review. Issue 26 (18th December 2022) - Kınacı-Biber, Esra; Önerge, Kübra; Mutlu, Akmer
Abstract: Purpose: The aim of this study was to evaluate gait characteristics, and the effectiveness of treadmill interventions on gait in infants and toddlers with Down syndrome (DS). Materials and Methods: A comprehensive search was performed on six databases for evidence published up to November 2020 for articles related to infants and toddlers with DS. The Clinical Appraisal Skills Programme Checklist assessed the methodological quality. Strength of evidence were evaluated Sackett's level. Results: Nine articles analyzing instrumental gait met the inclusion criteria. Of these, 4 compared DS and typically developing (TD), and 5 included treadmill training interventions for DS. Kinematic analysis was applied in 8 studies and all articles presented evaluations at different times according to the walking experience. Analysis with EMG was used in only one of the intervention articles and in 3 of the 4 comparative articles. Conclusions: Although similar improvements are seen in spatiotemporal parameters for toddlers with typical development and those with DS, the decrease in step width is not similar for DS. Early treadmill training can have a positively effect on the gait characteristics of DS infants. Further research should focus on the acquisition of gait characteristics, long-term evaluations, kinetics and EMG data, for these children. Implications For Rehabilitation: Toddlers with DS walked significantly slower, shorter stride length and less stride frequency. Treadmill training before 1-year old had positive effects on gait characteristics in infants and toddlers with DS. High-intensity treadmill training may provide early walking (2 months earlier) than the low-intensity group, therefore clinicians can add treadmill training programs in rehabilitation protocols of infants and toddlers with DS. Limited evidence for the effects of treadmill training on the kinematic and kinetic parameters of walking in DS infants and toddlers.